Manfaat Penerapan Enhanced Recovery After Surgery (ERAS) Pada Tatalaksana Perioperatif Kraniotomi - Ahmad Abdul Ghofar Abdulloh; Rheyma Sinar Al Fitri; Hana Zumaedza Ulfa; Devi Rahma Sofia; Ika Yuni Widyawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The application of the ERAS protocol perioperatively is considered to be able to improve the quality of perioperative care by reducing the problems caused by surgical procedures. The aim of this systematic review was to synthesize the evidence for the use of ERAS in craniotomy surgery patients. Five databases spanning 2017-2022 were used in this review, namely SAGE, Science Direct, Web of Science, PubMed and Scopus. Only articles using the RCT and CT designs were included in the review, the quality assessment of the articles used the JBI critical appraisal tools, the selection and extraction of articles were visualized using the PRISMA guidelines. There were 99 articles found, but only 8 articles met the inclusion criteria with a total of 1146 respondents. The main result of this review is to report the benefits of implementing the ERAS protocol on length of stay, cost of care, pain, patient satisfaction and perioperative complications. This review concludes that the implementation of the ERAS protocol can significantly help improve the recovery process of post-operative craniotomy patients. The results of studies regarding indicators of patient satisfaction in the pre-operative to post-operative process are still minimal, so that it can be considered to conduct studies on this matter in the future.Keywords: enhanced recovery after surgery; ERAS; length of stay; perioperative craniotomy ABSTRAK Penerapan protokol ERAS pada perioperatif dinilai dapat meningkatkan kualitas perawatan perioperatif dengan mereduksi masalah yang ditimbulkan oleh prosedur operasi. Tujuan dari systematic review ini adalah untuk mensintesis bukti-bukti penggunaan ERAS pada pasien bedah kraniotomi. Lima database dengan rentang tahun 2017-2022 digunakan dalam tinjauan ini, yakni SAGE, Science Direct, Web of Science, PubMed dan Scopus. Hanya artikel yang menggunakan desain RCT dan CT saja yang diikutkan ke dalam tinjauan, penilaian kualitas artikel menggunakan tools critical appraisal JBI, seleksi dan ekstraksi artikel divisualisasikan menggunakan pedoman PRISMA. Ditemukan 99 artikel, namun hanya terdapat 8 artikel yang memenuhi kiteria inklusi dengan jumlah total responden 1146. Hasil utama dari tinjauan ini adalah melaporkan manfaat penerapan protokol ERAS terhadap length of stay, biaya perawatan, nyeri, kepuasan pasien dan komplikasi perioperatif. Tinjauan ini menyimpulkan bahwa penerapan protokol ERAS secara signifikan dapat membantu meningkatkan proses pemulihan pasien post-operatif kraniotomi. Hasil studi mengenai indikator kepuasan pasien pada proses pre-operatif sampai post-operatif masih minimal, sehingga dapat dipertimbangkan untuk melakukan studi akan hal ini di masa mendatang.Kata kunci: enhanced recovery after surgery; ERAS; lama rawat inap; perioperatif kraniotomi